An analysis of arm propulsion in swimming - Rackham, G. W. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
Observation of the current methods of arm propulsion in the front crawl, back crawl, and butterfly strokes shows quite clearly a factor common to all strokes; ie., during the pulling phase, the hand deviates from a straight line track (when viewed from above). The purpose of this investigation was to observe this arm pull deviation from a straight line and to decide a) why it occurs, b) whether or not any advantage is obtained from its use, c) if it is advantageous, what mechanical principles are involved, and d) what influences if any could it have on training methods?